2021
DOI: 10.1111/jcmm.16547
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of tumour microenvironment‐related genes by TCGA database in rectal cancer

Abstract: Rectal cancer is a common malignant tumour and the progression is highly affected by the tumour microenvironment (TME). This study intended to assess the relationship between TME and prognosis, and explore prognostic genes of rectal cancer. The gene expression profile of rectal cancer was obtained from TCGA and immune/stromal scores were calculated by Estimation of Stromal and Immune cells in Malignant Tumors using Expression data (ESTIMATE) algorithm. The correlation between immune/stromal scores and survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Immune-related pathways, such as cytokine–cytokine receptor interactions, are also abnormally activated in tumors under hypoxia ( 26 ). Moreover, studies on CRC have shown that cytokine–cytokine receptor interaction is involved in changes in the tumor microenvironment and has a good guidance value in the prognosis and immunotherapy prediction of CRC patients ( 27 , 28 ). KEGG pathways and GO term enrichment of differentially expressed genes in patients between the high- and low-immune groups were also analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Immune-related pathways, such as cytokine–cytokine receptor interactions, are also abnormally activated in tumors under hypoxia ( 26 ). Moreover, studies on CRC have shown that cytokine–cytokine receptor interaction is involved in changes in the tumor microenvironment and has a good guidance value in the prognosis and immunotherapy prediction of CRC patients ( 27 , 28 ). KEGG pathways and GO term enrichment of differentially expressed genes in patients between the high- and low-immune groups were also analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…It is a potential cancer biomarker in cervical cancer [ 25 ] and in paediatric acute myeloid leukaemia [ 24 ], where its expression is also positively correlated with the expression of the actin-binding protein Plastin 3 [ 127 ]. In rectal cancer, MMRN1 is one of five hub genes that act as prognostic biomarkers and elevated MMRN1 expression is associated with poor prognosis [ 109 ]. MMRN1 downregulation is associated with chemoresistance in rectal cancer [ 111 ] and radiosensitivity and associated clinical outcome in gastric cancer [ 128 ].…”
Section: Mmrn1 Differential Expression In Cancermentioning
confidence: 99%
“…We used Human Protein Atlas (HPA) (https://www.pr oteinatlas.org/) tool to validate the mRNA and protein expression levels of the hub genes in all tissues. The Single Cell Type Atlas part in HPA as used to illustrate the expression of hub genes in single specific cell types [31].…”
Section: Specific Expression Analysis Of Hub Genes In Tissue and Cellsmentioning
confidence: 99%